CSR in rural areas : The case of SMEs in Central Bohemian Region - Nováková, Šárka (2019)
This thesis maps the development and understanding of Corporate SocialResponsibility in today’s world. In addition, it presents the most worrisomeproblems of rural areas in European Union and covers strategies and action plansthat the EU implements in order to solve these problems. One of the key pillarsof the strategies is the emphasis on SMEs and their role in the process ofdevelopment, which can be perceived as socially responsible. The author,therefore, interviews key players - business owners, state-funded institution andNGOs representatives in order to find what is the perception of CSR of businessowners and others in rural areas and how is it in line with the action plans andstrategies of the political representation. Furthermore, content analysis isperformed to understand the problem in more depth and identify the most burningissues.